2020
DOI: 10.1186/s12967-020-02230-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable scaffold implantation in STEMI patients: 5 years imaging subanalysis of PRAGUE-19 study

Abstract: Background: Bioresorbable scaffold (BRS) Absorb ™ clinical use has been stopped due to higher rate of device thrombosis. Scaffold struts persist longer than 2 years in the vessel wall. Second generation devices are being developed. This study evaluates long-term invasive imaging in STEMI patients.Methods: PRAGUE-19 study is an academic study enrolling consecutive STEMI patients with intention to implant Absorb ™ BRS. A total of 83 STEMI patients between December 2012 and March 2014 fulfilled entry criteria. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…And the physiological advantages of BRS, such as late lumen enlargement and vasomotion, are particularly appealing for coronary revascularization. However, evidence on the safety and efficacy of BRS vs. DES in patients with myocardial infarction is inconsistent; some trials (12)(13)(14) showed that BRS was similar to or better than DES on a device-oriented endpoint, while other trials reported that BRS was associated with higher risk TLR (15,16). Therefore, we conducted this systematic review and meta-analysis to compare the efficacy and safety of BRS vs. DES in patients with myocardial infarction undergoing percutaneous coronary interventions (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…And the physiological advantages of BRS, such as late lumen enlargement and vasomotion, are particularly appealing for coronary revascularization. However, evidence on the safety and efficacy of BRS vs. DES in patients with myocardial infarction is inconsistent; some trials (12)(13)(14) showed that BRS was similar to or better than DES on a device-oriented endpoint, while other trials reported that BRS was associated with higher risk TLR (15,16). Therefore, we conducted this systematic review and meta-analysis to compare the efficacy and safety of BRS vs. DES in patients with myocardial infarction undergoing percutaneous coronary interventions (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…Polimer malzeme teknolojisinin gelişmesiyle, yeni nesil stent üretimleri ve klinik çalışmaları başlamıştır [3,4]. Birinci nesil biyobozunur polimer esaslı stent tasarımları açık birim hücre modeline göre üretilmektedir.…”
Section: Introductionunclassified
“…However, the Absorb stent (Abbott Vascular, Santa Clara, CA, USA) was associated with a higher risk of target lesion revascularization and stent thrombosis compared with drug-eluting metallic stents in randomized trials [ 1 , 2 ] and in an acute myocardial infarction setting [ 3 ]. Furthermore, resorption only took place more than 3 years after implantation, being complete at 5 years [ 4 , 5 ]. Magnesium-based bioresorbable stents represent different technology with quicker resorption process and are sometimes viewed as second-generation bioresorbable stents.…”
Section: Introductionmentioning
confidence: 99%